Design and Development of SIMPENDA: A Web-Based Pension and Personnel Information System for Kudus Regency Agriculture and Food Office - Alvin Rainaldy Hakim (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study aims to design and develop a web-based Pension Information and Personnel Data System (SIMPENDA) as a digital solution for managing employee data and pension administration processes at the Kudus Regency Agriculture and Food Service. The system was developed using the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The results show that SIMPENDA is able to integrate all personnel and pension processes into one efficient and secure digital platform. This system provides convenience in managing employee data, calculating pensions, and tracking pension administration status in real time. Based on functional tests and user acceptance tests (UAT), all system features functioned well and obtained an average user satisfaction score of 4.65 out of 5, indicating excellent user acceptance. This system has been proven to improve administrative efficiency, data accuracy, and transparency of the pension process. In addition, SIMPENDA also supports the implementation of the Electronic-Based Government System (SPBE), in accordance with government policy to encourage the digitalization of public services. These findings not only benefit the Kudus Regency Agriculture and Food Service, but can also be used as a model for personnel digitalization in other regional government agencies, which is expected to improve the overall quality of public services.